Cumulative temporal association between assisted reproductive technology and childhood cancer: a systematic review and meta-analysis of observational studies - Jiang, Yanjie; Dai, Qiangqiang; Zhang, Shipeng; Wang, Hanyu; He, Xingyi; Fu, Rui; Tan, Junwen; Fu, Qinwei; Zhang, Qinxiu; Lu, Yan (Frontiers in Oncology, 2025)
ObjectiveAssisted reproductive technology (ART) has contributed to the birth of over 10 million children worldwide; however, its long-term health impacts, especially the potential risk of childhood cancer, continue to be a subject of debate. This study aims to examine the most current risk associations between ART and childhood cancer.MethodsWe conducted a comprehensive search across PubMed, Embase, Web of Science, and Cochrane Library databases up to August 1, 2024. These studies aimed to explore the association between ART and childhood cancer risk, covering overall cancers, haematological malignancies, neural tumors, other solid tumors, and 11 specific cancers. Pooled analyses of risk estimates and 95% confidence intervals were conducted using random effects models, while cumulative meta-analyses were conducted to provide a time-based summary of the evidence. The study was prospectively registered on PROSPERO (CRD42024547262).ResultsSixteen large sample observational studies were included. Our findings showed a 21% increased risk of overall cancer in children conceived via ART (relative risk [RR] = 1.21, 95% CI, 1.11–1.33), with elevated risks also noted for haematological malignancies (RR = 1.16, 95% CI, 1.05–1.28), neural tumors (RR = 1.19, 95% CI, 1.07–1.32), and other solid tumors (RR = 1.48, 95% CI, 1.26–1.73). Six specific cancer types also demonstrated higher risks. The direction and magnitude of the effects remained relatively constant over time, while the degree of precision increased as data from newer studies were incorporated. Sensitivity analyses confirmed the robustness of these findings, and no publication bias was found.ConclusionsOur findings suggest a potential risk association between ART and childhood cancer, raising concerns regarding the future application of ART. These findings are critical in informing infertile couples considering ART about the potential risks involved.Clinical trial registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024547262.